Between regulation and targeted expropriation: rural-to-urban groundwater reallocation in Jordan - Liptrot, T; Hussein, H (Water Alternatives Association, 2020)
In response to rising urban water demand, some regions have reallocated water from irrigation to more valuable uses. Groundwater over-exploitation, however, continues to degrade aquifer quality, and states rarely succeed at stopping overuse. This study asks whether growing urban requirements enable the reallocation of groundwater from irrigation to higher value added uses in domestic and industrial consumption. The paper is based on a series of interviews with policy makers and academics in Jordan, combined with data from remote sensing analysis. The results find that regulatory measures such as tariffs and well licensing have a limited impact on agricultural water use when opposed by a broad coalition of interest groups; instead, a targeted expropriation n a single small area, combined with an expansion of supply, did succeed in reallocating 35 million cubic metres of groundwater. The results suggest that urban water needs do increase state interest in reallocation. That reallocation was successful in only one of the attempted basins suggests that donor-region resistance is a major factor in reallocation outcomes. We discuss the strategy of, for future reallocators, targeting only aquifers with low political and enforcement costs.